Eyes are mirror of the brain: comparison of multiple sclerosis patients and healthy controls using OCT. (2nd September 2019) - Doğan, Ümit; Ulaş, Fatih; Türkoğlu, Şule Aydın; Ögün, Muhammed Nur; Ağca, Sümeyra
Abstract: Objective: To evaluate the thickness of choroid and retinal nerve fiber layer (RNFL) in multiple sclerosis (MS) patients with and without optic neuritis using enhanced depth imaging optical coherence tomography (EDI-OCT). Methods: In this cross-sectional study, both eyes of 52 MS patients [ n = 104 eyes; 62 eyes of MS patients without optic neuritis (MS-NON) and 42 eyes of MS patients with optic neuritis (MS-ON)] and only one eye of 36 healthy control subjects ( n = 36 eyes) were evaluated. Complete ophthalmologic examination and EDI-OCT scanning were completed for all participants. Choroidal thickness measurements were executed at three different points. Results: Choroidal thickness measurements were similar between MS patients and healthy control subjects. However, the mean subfoveal choroidal thickness was increased significantly in MS-ON group (399.13 ± 82.91 μm) compared to MS-NON group (342.71 ± 82.46 μm; p = 0.004). Mean RNFL thickness was significantly reduced in MS patients (90.42 ± 13.31 μm) compared to healthy controls (101.18 ± 10.75 μm; p < 0.001). Moreover, temporal RNFL thickness was significantly thinner in MS-ON group (54 ± 14.50 μm) than MS-NON group (62.15 ± 15.88 μm; p = 0.01). In MS patients, temporal RNFL thickness was correlated with both Expanded Disability Status Score ( r = 0.383; p < 0.001) and longer disease duration ( r =–0.202; p = 0.04). Conclusion: The results of the present study suggest that RNFL thickness can be used as an important parameter while following up with MS patients. However, more studies using EDI-OCT are required with larger MS patient groups and automated method.